Why do people attempt suicide? A mixed methods research from South India - Purushothaman, Punithakumary; Premarajan, Kariyarath Cheriyath; Ramachandran, Jayalakshmy; Thangaraj, Susila (International Journal Of Community Medicine And Public Health, 2019)
Background: Every 40 seconds a person dies by suicide. Suicide is the second leading cause of death among young people 15-29 years of age, globally. In India, there is an increasing trend of suicide from 10.4 per lakh in 2003 to 10.9 per lakh in 2009. Methods: A (QUAN – QUAL) sequential explanatory design was used. Among 200 patients admitted for attempted suicide in JIPMER and Indira Gandhi Government Hospital and Post Graduate Institute Pondicherry were assessed for the reasons for attempting suicide using a semi-structured questionnaire. For a subsample of 40 (20%) In-depth interview was done to explore and understand the reasons and the undermined situation associated with attempted suicide at their residence. Results: Among the study subjects (n=200), mean (±standard deviation) age of suicide attempt was 26±9.1 years. Commonest reason for attempting suicide was verbal abuse, most often by parents (31.9%). Other precipitating factors were physical abuse, illness, marital conflict, family related problem, etc. On IDI, it was found that there were several factors like, background factors, aggravating, and protective factor. A conceptual diagram was generated depicting the imbalance between the protective and aggravating factors acting on the background factors before the execution of a suicide attempt. Conclusions: There is lot of scope to reduce the suicidal attempts in our country. Opportunistic screening should be done to identify any psycho-social issues among patients attending OPD. Strong social support and enabling environment should be provided for counselling individuals with suicidal ideation and intentions.